Extrusion technologies of feed and food including biomass of insects (review) - V. I. Pakhomov; S. V. Braginets; O. N. Bakhchevnikov; A. S. Alferov; D. V. Rudoy (Аграрная наука Евро-Северо-Востока, 2020)
The review deals with the problems of extrusion of feed and food including biomass of insects. Inclusion of insects into the composition of feed and food increases their nutritional value through enrichment with protein and fat. Extrusion of the flour from ground and dried insects blended with vegetable raw material, generally presented by grinded grain, is most commonly used. However, the blend of crude larvae of insects and grinded vegetable raw materials can be also successfully extruded. Specific regularities of processes of insect biomass and vegetable raw material extrusion have been developed. It has been established, that with increase in insect content in the extrudate, its color becomes darker, the surface less smooth, the structure more layered. The hardness declines, the value of water absorption index decreases, the value of water solubility index and its moisture content increase. Variation in the rate of raw material feed into the extruder allows to change the properties of a finished extrudate. As the value of raw materials feed increases, the water absorption index of the extrudate and its moisture content decrease, but the water solubility index increases. Rational parameters of the extrusion process general for all blends of vegetable raw materials and insect biomass as well as the nature of their influence on properties of finished extrudate have not been determined yet. The problem of extrusion raw materials for the production of feed and food containing biomass of insects is promising but requires carrying out supplementary studies.